(untitled) - Peters, B. Guy (Chatham, N.J., 1996)
This is the new edition of an undergraduate level textbook on the formation and implementation of public policy in the United States. Peters (American government, U. of Pittsburgh) describes the structure of the policy-making system and the process by which policy is enacted.
Keywords: Policy sciences,Khoa học hoạch định chính sách,Political planning,Lập kế hoạch chính trị; United Stated,Hoa Kỳ